Gender at Work at Home: Family Decisions, the Labour Market, and Girls' Contributions to the Family Economy - Bradbury, Bettina (Canadian Family History. Selected Readings, 1992)
Keywords: Enfants; Famille; Femmes; Travail

The Family Economy and Work in an Industrializing City: Montreal in the 1870s - Bradbury, Bettina (Cities and Urbanization. Canadian Historical Perspectives, 1990)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

The Family Economy and Work in an Industrializing City, Montreal in the 1870's - Bradbury, Bettina (Interpreting Canada's Past. Vol. 2: Post-Confederation, 1993)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

Women and Wage Labour in a Period of Transition: Montreal, 1861-1881 - Bradbury, Bettina (Canadian Labour History: Selected Readings, 1994)
NOTICE DG
Keywords: Famille; Femmes; Travail